Pengaruh Kedisiplinan Terhadap Efektivitas Kinerja Anggota Dewan DPRD Kabupaten Badung Tahun 2014-2015 - Purwa Atmaja, I Gede Pasek (CITIZEN CHARTER, 2017)
The purpose of this study is to measure how far the influence of discipline on the performance effectiveness of DPRD members of Badung Regency 2014-2015. The research method used is quantitative method. Primary data in this study was obtained through the distribution of questionnaires to all members of the DPRD Badung regency which amounted to 40 people.The results showed that the discipline had a positive effect on the effectiveness of the performance of Badung District People's Legislative Assembly (DPRD) with the result of R2 of 0,380, which means that the effectiveness of Member's performance is influenced by discipline of 38%. The results of simple linear regression calculations show that if the discipline increased 1%, then the effectiveness of performance will rise by 0.616. Whereas if the discipline does not change or equal to zero, then the total effectiveness of performance in the DPRD Badung regency of 12.997. Based on result discipline have positive and significant effect to performance effectivity at DPRD Badung Regency. Keywords: Discipline, Performance Effectiveness, DPRD